Excessive Erythrophagocytosis Accounts for Systemic Inflammation in Chronic Kidney Disease - Meng Q; Yang X; Liu Z; You G; Chen W; Zhao B; Zhu H; Xu L; Zhou Y; Liu X; Zhai C; Wang R; et al. (Dove Medical Press, 2024)
Qian Meng,1,* Xiaowei Yang,1,* Zhongcheng Liu,2 Guoxing You,3 Wanyi Chen,3 Bing Zhao,1 Huizi Zhu,4 Liang Xu,1 Yan Zhou,1 Xiang Liu,1 Chunjuan Zhai,5 Rong Wang,1 Lian Zhao,3 Jing Sun1 1Department of Nephrology, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, 250021, People's Republic of China; 2Department of Cardiovascular, The North City Hospital of Jinan, Jinan, Shandong, 250031, People's Republic of China; 3Academy of Military Medical Sciences, Beijing, 100850, People's Republic of China; 4Department of Nephrology, Fuyang People's Hospital, Fuyang, Anhui, 236000, People's Republic of China; 5Department of Cardiology, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, 250021, People's Republic of China*These authors contributed equally to this workCorrespondence: Jing Sun, Department of Nephrology, Shandong Provincial Hospital Affiliated to Shandong First Medical University, 324 Jingwu Road, Jinan, Shandong, 250021, People's Republic of China, Tel +86 151 6888 6367, Email sunj5708@126.com Lian Zhao, Academy of Military Medical Sciences, 27 Taiping Road, Beijing, 100850, People's Republic of China, Tel +8613671217095, Email zhaolian@bmi.ac.cnPurpose: Chronic kidney disease (CKD) is associated with persistent systemic inflammation. Reduced red blood cell (RBC) survival in patients with CKD has been identified for several decades. The purpose of this study is to explore whether excessive erythrophagocytosis exists and contributes to systemic inflammation in CKD.Patients and methods: A CKD rat model was induced by 5/6 nephrectomy. Erythrocyte osmotic fragility was determined with hypotonic NaCl solutions. Erythrocyte deformability was evaluated by filterability. RBC cell death was quantified using fluorescence-activated cell sorting analyses of fluorescent annexin V-bound surface phosphatidylserine (PS). Erythrophagocytosis was evaluated in vivo and in vitro. RT-qPCR and immunohistochemistry were used to determine the inflammatory effects after erythrophagocytosis.Results: Erythrocyte osmotic fragility and deformability progressively declined, and the percentage of PS-exposing RBCs progressively increased in CKD rats. Levels of erythrophagocytosis in vivo were evaluated by autologous injection of CFSE-labeled erythrocytes. In comparison with the control group, higher fluorescence intensity of CFSE was detected in the spleen homogenates of rats with CKD. In vitro, more of erythrocytes from 5/6Nx rats were phagocytosed by peritoneal macrophages in comparison to those from control rats. Compared with macrophages phagocytosed control erythrocytes, macrophages phagocytosed CKD erythrocytes exhibited higher mRNA levels of IL-6, CXCL-10, CXCL-11, iNOS, IL-1β, ICAM-1 and MCP-1. Compared with the control group, the red pulp of rats with CKD exhibited higher levels of p-NFκB, IL-6, iNOS and CXCL-10. ELISA results showed significantly increased plasma levels of both IL-6 and CXCL-10 in patients with long-term hemodialysis compared with those in healthy controls (2.30 ± 1.38 pg/mL vs 1.33 ± 0.65 pg/mL, P=0.01; 78.11 ± 27.34 pg/mL vs 37.45 ± 7.08 pg/mL, P=0.001).Conclusion: Our results indicated that excessive erythrophagocytosis may contribute to systemic inflammation in CKD. Keywords: chronic kidney disease, chronic inflammation, erythrocyte, phagocytosis